UJI DIAGNOSTIK PLATELET TO LYMPHOCYTE RATIO (PLR) PADA PASIEN SEPSIS DEWASA DI RUMAH SAKIT SAIFUL ANWAR MALANG - Karina Nilasari; Agustin Iskandar (CHMK HEALTH JOURNAL, 2021)
Background: Sepsis, is a major health problem throughout the world, as evidenced by the high incidence, mortality, health costs needed to manage a patient with sepsis, as well as an increase in the incidence of these events annualy. Platelet Lymphocyte Ratio (PLR) is a new prognostic marker that integrates risk predictions from two parameters, namely platelets and lymphocytes into one, which is commonly used as a marker for aggregation and inflammatory pathways. The purpose of this study was to determine the diagnostic value of PLR on sepsis. Method: Platelet lymphocyte ratio (PLR) was calculated in 100 adult patients who met the inclusion criteria, consisting of 70 sepsis patients and 30 normal adult patients. The diagnosis of sepsis is based on the Sepsis-related Organ Failure Assessment (SOFA) scoring system. Results: The ROC curve showed AUC 0.900 (95% Confidence Interval: 83.9% - 96.2%, p = 0,000) and the best cut-off value from PLR to predict sepsis was greater or equal to 141.9 with sensitivity: 85 , 7% and specificity of 86.7%, and PPV values ​​of 93.8% and NPV of 72.2%. Conclusion: PLR has a good diagnostic value in determining sepsis in adult patients Keywords: PLR, sepsis